PRAKTIK JUAL BELI PADI DENGAN SISTEM TEBAS DAN IJON MELALUI PERANTARA DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM: Studi Kasus di Wilayah Desa Mekarjaya Kecamatan Gantar Kabupaten Indramayu - Hendra Gunawan; Ahmad Asrof Fitri (Melati Institute, 2022)
This research is based on the buying and selling activities carried out by most rice farmers in Mekarjaya village, Gantar District, Indramayu Regency, that there are transactions for buying and selling slashes and ijon on rice bag commodities, where in practice transactions are carried out on rice that does not yet appear mature so that plucking is carried out until waiting for the harvest period to arrive or we often know the ijon system. Another thing in this transaction process is that every transaction must go through a regional intermediary, where this intermediary is a person who will bridge between the slasher, seller and buyer with the rice farmer who is specifically in the Mekarjaya Village area, Gantar District, Indramayu Regency. Theamount of wages is usually carried out by agreement and voluntarily both parties. The purpose of this thesis is to find out the views of positive law and Islamic law on the practice of buying and selling rice carried out by the people of Mekarjaya Village. The research methods used by researchers are qualitative approaches and types of field research. The data collection techniques used in this study were in the form of observations, interviews, and conducting studies on natural situations. Meanwhile, data analysis techniques use data reduction, data presentation (data display), and drawing conclusions. From the research that has been carried out by the author, the following results were obtained: that the transaction of buying and selling slashes and ijon on rice through intermediaries that occurred in Mekarjaya Village, Gantar District, Indramayu Regency, was invalid according to the provisions of Islamic law and Positive Law because the sale and purchase transaction was through intermediary services with benefits that already had a price value, but in the form of, size, and its nature is still not clearly and perfectly visible on the object being traded. However, in terms of obtaining wages obtained from a realtor / intermediary in selling slashed goods (rice) is in accordance with the provisions of Islamic law, namely the wages obtained by the realtor from the buyer / slasher are also entitled to be received as a thank you for being shown and given slashed goods / merchandise which will later be resold to get profits on a voluntary basis.